2017
DOI: 10.1111/ddi.12668
|View full text |Cite
|
Sign up to set email alerts
|

In search of relevant predictors for marine species distribution modelling using the MarineSPEED benchmark dataset

Abstract: Aim Ideally, datasets for species distribution modelling (SDM) contain evenly sampled records covering the entire distribution of the species, confirmed absences and auxiliary ecophysiological data allowing informed decisions on relevant predictors. Unfortunately, these criteria are rarely met for marine organisms for which distributions are too often only scantly characterized and absences generally not recorded. Here, we investigate predictor relevance as a function of modelling algorithms and settings for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 89 publications
(143 reference statements)
3
58
1
Order By: Relevance
“…This index measures model accuracy for presence‐only test data against a geographical‐environmental background. We calculated the Boyce index for the modeled presences, and also for an additional set of presences retrieved from the MarineSPEED dataset (Bosch, Tyberghein, Deneudt, Hernandez, & Clerck, ), as an external evaluation of the models.…”
Section: Methodsmentioning
confidence: 99%
“…This index measures model accuracy for presence‐only test data against a geographical‐environmental background. We calculated the Boyce index for the modeled presences, and also for an additional set of presences retrieved from the MarineSPEED dataset (Bosch, Tyberghein, Deneudt, Hernandez, & Clerck, ), as an external evaluation of the models.…”
Section: Methodsmentioning
confidence: 99%
“…Depth was an important predictor, as shown by Bosch et al. (2018) and Snickars et al. (2014) who suggested that bathymetry is of high relevance for modelling various taxa.…”
Section: Discussionmentioning
confidence: 84%
“…Water temperature has been identified as the most relevant predictor of global marine species distribution and land distance of moderate importance for both benthic and planktonic species (Bosch, Tyberghein, Deneudt, Hernandez, & De Clerck, 2018;Bradie & Leung, 2017). Depth was an important predictor, as shown by Bosch et al (2018) and Snickars et al (2014) who suggested that bathymetry is of high relevance for modelling various taxa. Ice thickness was moderately important for phytobenthos and zooplankton, perhaps reflecting limits on distribution of the former due to ice abrasion, changes in light exposure and a preference of ice-free waters for the latter (Clark et al, 2013;Kube, Postel, Honnef, & Augustin, 2007;Pascual et al, 2015;Richardson, 1979).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Stationarity and convergence of runs was assessed visually using For all specimens, we collected mean sea surface temperature (SST mean) based on locality information and environmental layers present in Bio-Oracle v2.0 (Assis et al 2018). Averaged mean surface temperatures correlate equally well or better with marine species distribution ranges compared to average minimum or maximum temperatures as demonstrated by Bosch et al (2018). Ancestral states of SST affinities were reconstructed and visualised on the phylogeny using the fastAnc and contMap functions of the R package phytools (Revell 2012).…”
Section: Methodsmentioning
confidence: 99%